Information security problems in modern society - Nusipova А.У. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
There is no doubt that the rapid development of information and communication technologies (ICT) and a sharp increase in the role of information in all spheres of society is the main trend. In democracies, information management and communication between government and society is central. Today, the active development of ICT has reduced the distance between the political elite and civil society. Information has turned into a political resource with qualitatively new properties that can be used very effectively in the political sphere. The influence of information in any form on all spheres of public life, politics, economics, and culture predetermines the relevance of the processes of formation and implementation of state information policy. As enterprises and government agencies increasingly adopt cloud, mobile, and social computing, information technology (IT) environments are becoming more difficult to defend. Increasingly, organizations need to accept that security breaches are inevitable. Security strategies need to go beyond defense to include detection, response, and recovery. All this gives rise to a need for new skills and approaches and specialized tools and services, including continuous monitoring and threat forensics powered by analytics. Taking into account the interrelation of these factors, the article examines the issues of studying public perception of information security in various spheres of the Republic of Kazakhstan.